Immunobiologicals in dermatology - Dimitri Luz Felipe da Silva; Elisa Nunes Secamilli; Mariana Valbon Beleli; Juliana Yumi Massuda; Andrea F.E.C. Franca; Renata F. Magalhães (Sociedade Brasileira de Dermatologia, 2022)
Abstract Immunobiologicals are a reality in current clinical practice and have increasingly gained space in the inflammatory disease scenario, especially in dermatology, with approved drugs for psoriasis, atopic dermatitis, and hidradenitis suppurativa, in addition to many others undergoing study. It is important for dermatologists to have knowledge of the medications approved in Brazil, for the best management of dermatoses, in addition to the fact that they represent hope for improvement in patients with chronic diseases.